The Burden of Obesity in Egypt - Aboulghate, Mohamed; Elaghoury, Aliaa; Elebrashy, Ibrahim; Elkafrawy, Nabil; Elshishiney, Galal; Abul-Magd, Ehab; Bassiouny, Engy; Toaima, Dalia; Elezbawy, Baher; Fasseeh, Ahmad; Abaza, Sherif; Vokó, Zoltán (Frontiers in Public Health, 2021)
Objective: Estimating the burden of obesity to society is an essential step in setting priorities and raising awareness. We aimed to assess the clinical, humanistic and economic burden of obesity for adults in Egypt. Methods: We used the population attributable fraction concept to estimate the burden. A non-systematic review was conducted to estimate the prevalence of obesity and its comorbidities in addition to the obesity attributable fraction. Patient numbers, direct healthcare costs, disability adjusted life years (DALYs) and attributable mortality were estimated. Results: Obesity is a major contributor to the development of diabetes mellitus, hypertension, obstructive sleep apnea and fatty liver, in addition to several serious diseases. The estimated annual deaths due to obesity was about 115 thousand (19.08% of the total estimated deaths in 2020). DALYs attributable to obesity may have reached 4 million in 2020.The economic burden imposed by obesity is around 62 Billion Egyptian pounds annually. This value is the cost of treating diseases attributable to obesity in adults. Conclusions: Diseases attributable to obesity create a huge economic, humanistic, and clinical burden in Egypt. Reducing obesity could help dramatically decrease the catastrophic health effect of these diseases which in turn decreases mortality and DALYs lost.